Novel bisthiazole ligand and its copper(II) complex with unusual seven membered ring: Synthesis, characterization, experimental and theoretical study of the effect of ligand flexibility, and antimicrobial activity. (15th November 2021) - Velluti, Francesca; Acevedo, Ana; Serra, Gloria; Ellena, Javier; Borthagaray, Graciela; Facchin, Gianella; Scarone, Laura; Alvarez, Natalia; Torre, María H.
Graphical abstract: A novel bisthiazole ligand and its copper(II) complex were synthetized. Single crystal X-ray diffraction of complex evidence a pentacoordinated copper center forming 5 and 7 membered rings. Structure packing was analyzed by means of Hirshfeld surfaces and FTIR frequencies were calculated. Antimicrobial activity was determined against bacteria and C. albicans. Abstract: In the search of antimicrobial agents a novel bisthiazole ligand containing a methylamine linker (ethyl 2-((2-methylthiazole-4-yl)methylamino)thiazole-4-carboxylate (BTa) and its copper(II) complex [CuCl2 BTa]·2H2 O were synthetized. Both compounds were characterized by analytical and spectroscopic methods. Single crystal X-ray diffraction of copper complex evidence a pentacoordinated copper(II) center of intermediate geometry forming 5 and 7 membered chelate rings with BTa acting as a tridentate ligand leaving the amine NH group in the thiazole linker available for participation in intermolecular interactions. Structure packing was analyzed by means of Hirshfeld surfaces, 2D fingerprint plots and lattice interaction energies were assessed. In order to deepen the understanding of the coordination to the flexible ligand DFT studies were carried out at the B3LYP/LANL2DZ level of theory. Calculated FTIR frequencies were used to perform a Vibrational Energy Distribution Analysis (VEDA) where potential energy distribution of vibrational was determined. Minimum inhibitory concentrations for BTa and CuBTa on E. coli ATCC 25922, S. aureus ATCC 25923, P. aeruginosa ATCC 9027 and C. albicans ATCC 10231 were determined.